2020
DOI: 10.20945/2359-3997000000254
|View full text |Cite
|
Sign up to set email alerts
|

Different amounts of moderate to vigorous physical activity and change in glycemic variability in adolescents with type 1 diabetes: is there dose-response relationship?

Abstract: Objective: To identify the level of physical activity and glycemic variability of adolescents with type 1 diabetes mellitus and to compare glycemic variability on days with different amounts of moderate to vigorous physical activity (MVPA). Subjects and methods: A sample of 34 subjects aged 10 to 15 years, 18 (52.94%) female; age: 13.04 ± 1.94; HbA1c: 9.76 ± 1.51. Physical activity was measured by wGT3X accelerometer. The glucose data were obtained using continuous glucose monitoring, and the following glycemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
1
6
2
Order By: Relevance
“…But our study does not align with at least one other cross‐sectional study observing that the amount of physical activity performed by an adolescent with T1D does not impact various CGM metrics, such as the mean glucose, the low blood glucose index or the high blood glucose index significantly 25 . In that previous study, 25 however, glycemia was only shown to be comparable between active days and sedentary days within a child, while we determined if the activity levels on active days influences glycemia across the cohort. Based on our findings, we propose that each 200 MET‐minute increase in daily activity (roughly equivalent to 30 min of vigorous exercise) on active days, one to two times per week, may be associated with a 7% increase in TIR for a child living with T1D who is not meeting current physical activity guidelines.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…But our study does not align with at least one other cross‐sectional study observing that the amount of physical activity performed by an adolescent with T1D does not impact various CGM metrics, such as the mean glucose, the low blood glucose index or the high blood glucose index significantly 25 . In that previous study, 25 however, glycemia was only shown to be comparable between active days and sedentary days within a child, while we determined if the activity levels on active days influences glycemia across the cohort. Based on our findings, we propose that each 200 MET‐minute increase in daily activity (roughly equivalent to 30 min of vigorous exercise) on active days, one to two times per week, may be associated with a 7% increase in TIR for a child living with T1D who is not meeting current physical activity guidelines.…”
Section: Discussioncontrasting
confidence: 99%
“…The present study supports previous work suggesting that adolescents with T1D who accumulate ~60 min of physical activity on three or more days per week have better glucose control, as measured by HbA1c levels, when compared to those who accumulate less activity 23,24 . But our study does not align with at least one other cross‐sectional study observing that the amount of physical activity performed by an adolescent with T1D does not impact various CGM metrics, such as the mean glucose, the low blood glucose index or the high blood glucose index significantly 25 . In that previous study, 25 however, glycemia was only shown to be comparable between active days and sedentary days within a child, while we determined if the activity levels on active days influences glycemia across the cohort.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…CGM data have been used to better help understand the relationship between daily activities, behaviors, and glucose control including diets and eating patterns [34][35][36][37][38][39], exercise or activities [40][41][42][43][44][45][46][47][48][49][50], sleep [51][52][53], amount of time spent at home (eg, before and during the COVID-19 lockdown) [54], and externalizing behaviors [55].…”
Section: Using Cgm To Identify Relationships Between Daily Factors and T1d Symptoms And Behaviorsmentioning
confidence: 99%
“…Whether similar results would be observed in a pediatric population with type 1 diabetes mellitus is unknown. To our knowledge, only one study has looked specifically at the relationship between glucose variability and intensity levels of exercise or physical activity duration [ 16 ]. However, prior investigations have not examined this relationship in a habitually active pediatric population with type 1 diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%